Plants as a Letter of the “Alphabet of Human Thought” - Gambarova, Afaq (The Lingua Spectrum, 2026)
The article examines the concept of the plant as one of the universal units of the “alphabet of human thought.” Based on religious texts, myths and cultural traditions of different peoples, the study shows that the plant world has long been connected with food, knowledge, punishment, healing and spiritual symbolism. Special attention is paid to the image of the tree in Abrahamic religions, Khanty myths, Greek tradition, Tengrism, Chinese mythology and folk beliefs. The plant is interpreted not only as a part of nature, but also as a cultural sign reflecting the connection between human beings, earth, sky, life, death and moral choice. The article emphasizes the need for a harmonious attitude toward nature and the preservation of ecological balance. The research demonstrates that the concept of the plant occupies an important place in the linguistic worldview and may be regarded as a universal semantic unit of human culture.